Taxonomic Status of Genus Nepeta L. (Lamiaceae) in Kashmir Himalaya, India - Hassan, Tauheeda; Dar, G.H. (Indian Forester, 2013)
During survey of Kashmir Himalaya twenty two species of Nepeta were recorded of which twelve were from Kashmir region and remaining from Ladakh region. The species recorded are; N. annua, N. cataria, N. campestris, N. clarkei, N. coerulescens, N. connata, N. discolor, N. elliptica, N. eriostachys, N. kokanica, N. laevigata, N. linearis, N. nervosa, N. paulsenii, N. podostachys, N. raphanorhiza, N. floccosa, N. longibracteata, N. glutinosa, N. govaniana, N. erecta and N. salviaefolia. Some species like N. elata, N. royleana, N. pamirensis and N. vakanica are synonyms of N. laevigata, N. salviaefolia, N. kokanica and N. floccosa respectively which were considered as separate species. N. leucophylla of Dehradun Herbarium has not been found in our study area. This species perhaps has been confused earlier with our N. salviaefolia.